Angiogenic potential of spheroids from umbilical cord and adipose-derived multipotent mesenchymal stromal cells within fibrin gel. (21st May 2018) - Gorkun, A A; Shpichka, A I; Zurina, I M; Koroleva, A V; Kosheleva, N V; Nikishin, D A; Butnaru, D V; Timashev, P S; Repin, V S; Saburina, I N
Abstract: One of the essential goals in regenerative medicine is microvascularization which enables an effective blood supply within de novo constructed tissues and organs. In our study, we used two common multipotent mesenchymal stromal cell (MMSC) sources (subcutaneous adipose tissue and Wharton's jelly of the umbilical cord) where is a subpopulation of endothelial precursors. In the medium supplemented with VEGF, the 3D cultures of UC MMSCs and ADSCs promoted the endothelial cell differentiation. To evaluate their ability to form a capillary-like network, we encapsulated spheroids within non-modified and PEGylated fibrin hydrogels. The PEGylated hydrogel supported better the formation of multibranched cords than the pure fibrin gel. Analysis of tubule growth rate, length, and branching showed that the differentiated ADSCs had higher angiogenic potential than the differentiated hUC MMSCs. Our study can be a basis for the development of new strategies in tissue engineering and treatment of vascular diseases.